2019
DOI: 10.2147/opth.s189071
|View full text |Cite
|
Sign up to set email alerts
|

<p>Three-year outcomes of combined trabecular micro-bypass and phacoemulsification in a predominantly Hispanic population with primary open-angle glaucoma</p>

Abstract: Purpose: To present long-term, real-world outcomes after implanting one trabecular micro-bypass stent with cataract surgery for primary open-angle glaucoma (POAG) in a predominantly Hispanic patient population. Patients and methods: This retrospective, consecutive case series evaluated intraocular pressure (IOP), medications, and safety through 36 months after implanting one iStent ® during phacoemulsification cataract surgery. Eyes were stratified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…To date, the safety and performance of iStent trabecular micro-bypass have been established by a breadth of studies evaluating the device, including in standalone implantation or in combination with cataract surgery or other MIGS procedures, in both single-and multiple-stent usage, in populations with various levels of disease severity, and in various subtypes of glaucoma and ocular hypertension. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The stent has been widely adopted and studied by surgeons around the world. 43 However, iStent outcomes have not been as closely examined in Japanese populations.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the safety and performance of iStent trabecular micro-bypass have been established by a breadth of studies evaluating the device, including in standalone implantation or in combination with cataract surgery or other MIGS procedures, in both single-and multiple-stent usage, in populations with various levels of disease severity, and in various subtypes of glaucoma and ocular hypertension. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The stent has been widely adopted and studied by surgeons around the world. 43 However, iStent outcomes have not been as closely examined in Japanese populations.…”
Section: Discussionmentioning
confidence: 99%
“…With up to 7 years of postoperative follow-up, iStent studies have often focused on patients with mild to moderate POAG undergoing cataract surgery, but an increasing number of studies have assessed iStent for different glaucoma types (eg, pseudoexfoliative, angle-closure, pigmentary), more advanced severity, standalone cases, and in combination with other procedures or stents. [11][12][13][14][15][16][17][18][19][20][21][22][23] The more recent iStent inject ® Trabecular Micro-Bypass (CE Mark 2010, FDA approval 2018) contains two stents that create two patent bypasses through the diseased trabecular meshwork. This device has been studied both with and without concomitant cataract extraction, and in studies with up to 5 years of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Fechtner et al also reported incrementally higher OSDI scores in patients using more glaucoma medications, with mean OSDI scores of 12.9, 16.7, and 19.4 in eyes on one, two, and three glaucoma medications, respectively [9]. Alongside such studies correlating medications with ocular surface disease, the medication reductions consistently observed after stent implantation also are well known and widely documented [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Thus, it stands to reason that stent implantation would result in ocular surface improvement.…”
Section: Discussionmentioning
confidence: 92%
“…1a) is a 12-item subjective questionnaire designed to assess a patient's symptoms related to chronic dry eye, its severity, and its impact on ability to function [32]. OSDI scores range from 0 to 100, with severity defined as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and severe (33-100). The Oxford Schema (Fig.…”
Section: Osd Testing Protocolsmentioning
confidence: 99%
See 1 more Smart Citation